2007
DOI: 10.1037/0012-1649.43.5.1051
|View full text |Cite
|
Sign up to set email alerts
|

Young children associate novel words with complex objects rather than salient parts.

Abstract: How do children learn associations between novel words and complex perceptual displays? Using a visual preference procedure, the authors tested 12-and 19-month-olds to see whether the infants would associate a novel word with a complex 2-part object or with either of that object's parts, both of which were potentially objects in their own right and 1 of which was highly salient to infants. At both ages, children's visual fixation times during test were greater to the entire complex object than to the salient p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 65 publications
1
27
0
1
Order By: Relevance
“…On the basis of similar results, Nazzi (2005) argued that, given that the names are the only reliable cues to categorization in the task, the fact that infants are performing above chance level in the current task implies that (a) they have learned the associations between the names and the objects during the presentation phase and that (b) they are able to use these associations to group objects together during the test phase. This ability to associate objects and names was interpreted as (a necessary step to) word learning, in line with other studies on early word learning (Hollich, Golinkoff, & Hirsh-Pasek, 2007;Houston-Price, Plunkett, & Duffy, 2006;Nazzi, 2005;Nazzi & New, 2007;Stager & Werker, 1997;Swingley & Aslin, 2007;Werker et al, 2002), all of which show that infants retain object-name associations for the duration of the experimental task/trial but do not evaluate whether these associations are retained in long-term memory (for evidence suggesting that retention is limited even by 24 months of age, see Horst & Samuelson, 2008). Accordingly, Nazzi (2005) concluded that the bias found with this name-based categorization task had to do with lexical acquisition.…”
Section: Discussionmentioning
confidence: 87%
“…On the basis of similar results, Nazzi (2005) argued that, given that the names are the only reliable cues to categorization in the task, the fact that infants are performing above chance level in the current task implies that (a) they have learned the associations between the names and the objects during the presentation phase and that (b) they are able to use these associations to group objects together during the test phase. This ability to associate objects and names was interpreted as (a necessary step to) word learning, in line with other studies on early word learning (Hollich, Golinkoff, & Hirsh-Pasek, 2007;Houston-Price, Plunkett, & Duffy, 2006;Nazzi, 2005;Nazzi & New, 2007;Stager & Werker, 1997;Swingley & Aslin, 2007;Werker et al, 2002), all of which show that infants retain object-name associations for the duration of the experimental task/trial but do not evaluate whether these associations are retained in long-term memory (for evidence suggesting that retention is limited even by 24 months of age, see Horst & Samuelson, 2008). Accordingly, Nazzi (2005) concluded that the bias found with this name-based categorization task had to do with lexical acquisition.…”
Section: Discussionmentioning
confidence: 87%
“…This induction is logically not possible when a child encounters a new word for the first time because there are too many possible ways of generalization from a single exemplar [45]; however, this is exactly what children face when they learn words [46][47][48].…”
Section: The Induction Problem In Word Learning and Sound Symbolism Bmentioning
confidence: 99%
“…Just as there are constraints on memory flexibility during the second year of life, there are also constraints on label learning. For example, 12-month-olds will map non-verbal mouth noises (e.g., "psst") to objects using an interactive preferential looking paradigm (Hollich, Golinkoff, & Hirsh-Pasek, 2007). Between 12 and 24 months, infants begin to limit what they will accept as a symbol-object pairing; by 2 years, they will only accept words and no longer map non-symbolic sounds or gestures to objects (e.g., Graf Estes, Antovich, & Hay, 2018;Graham & Kilbreath, 2007;Namy & Waxman, 1998).…”
Section: Research Highlightsmentioning
confidence: 99%